THE EFFECT OF BIG DATA APPLICATION ON FINANCIAL PERFORMANCE: COMPANY SIZE AS A MODERATING VARIABLE - Khasanah, Aniatul; Hudaya, Robith (Jurnal Aplikasi Akuntansi, 2024)
This research aims to determine the effect of implementing big dataon a company's financial performance by considering company size as a moderating factor. This research focuses on the banking sector, which is publicly traded on the IDX. The sampling technique used was purposive sampling over three years (2020-2022). 46 out of 47 companies were selected for sampling and observation. The analysis tool uses Eviews 12 to perform panel data regression. Research findings show that the use of big data has an adverse impact on the financial performance of businesses. Apart from that, the size of the company is also considered not to have the ability to mitigate the impact of the use of big data on the company's financial performance.